CHALLENGES OF REGIONAL SECURITY FOR CENTRAL AND EASTERN EUROPEAN COUNTRIES - LYZUN, Mariia; LISHCHYNSKYY, Ihor; VITÁLIŠOVÁ, Katarína; BORSEKOVÁ, Kamila (Journal of European Economy, 2025)
The paper analyzes the challenges of regional security for the countries of Central and Eastern Europe (CEE) in the context of modern geopolitical changes, particularly Russian aggression against Ukraine. The impact of security threats on the region’s economic development, trade flows, and political stability is examined. Emphasis is placed on the importance of regional cooperation through formats such as the Visegrad Group, the Lublin Triangle, the Weimar Triangle, and the Bucharest Nine. The article explores changes in the defense budgets of CEE countries, their role in transforming energy policy, and their support for Ukraine. Adjustments in defense spending, made in response to growing security threats, are analyzed. Mechanisms for reorienting trade flows between CEE countries and Ukraine in the context of war are also studied. The authors highlight the importance of Ukraine’s integration into the EU and NATO as a strategic element of European stability. Measures are proposed to strengthen regional cooperation, particularly in the areas of defense, energy, and economic policy. A roadmap has been developed to ensure long-term regional security by enhancing cooperation within the EU and NATO, countering Eurosceptic narratives, and integrating Ukraine into European and Euro-Atlantic structures. JEL: F02, F10, F15, F42, H56, O52.